Cuban policosanol improves high-density lipoprotein cholesterol efflux capacity in healthy Japanese subjects - Uehara, Yoshinari; Komatsu, Tomohiro; Sasaki, Kei; Abe, Satomi; Nakashima, Shihoko; Yamamoto, Taiki; Kim, Ji-Eun; Cho, Kyung-Hyun (Frontiers in Nutrition, 2024)
Policosanol supplementation has been reported to increase high-density lipoprotein (HDL)cholesterol (HDL-C). However, the association between Cuban policosanol supplementation and HDL cholesterol efflux capacity (CEC), an important function of HDL, remains unclear. We performed a lipoprotein analysis investigating 32 Japanese healthy participants (placebo, n = 17 or policosanol supplementation for 12 weeks, n = 15) from a randomized Cuban policosanol clinical trial. First, HDL CEC and HDL-related factors were measured before and after policosanol supplementation. Then, through electron microscopy after ultracentrifugation and high-performance liquid chromatography, HDL morphology and subclass were analyzed, respectively. Finally, the effects of policosanol supplementation regarding HDL function, HDL-related factors, and HDL morphology/component were examined. Cuban policosanol considerably increased the HDL CEC and HDL-C and apolipoprotein A-I (ApoA-I) levels. Furthermore, policosanol supplementation led to larger HDL particles, increased cholesterol content in larger HDL particles, and reduced triglyceride content in smaller HDL particles. In participants with high baseline HDL-C levels, the policosanol effects for HDL CEC are observed. HDL CEC fluctuation induced by policosanol was highly associated with HDL-C and ApoA-I changes. In conclusion, for the first time, we demonstrated that policosanol supplementation increased the HDL CEC in healthy participants.